Integrated care teams in primary care improve clinical outcomes and care processes in patients with non-communicable diseases - Pei Lin Hu; Cynthia Yan-Ling Tan; Ngoc Hoang Long Nguyen; Rebekah Ryanne Wu; Juliana Bahadin; Nivedita Vikas Nadkarni; Ngiap Chuan Tan (Singapore Medical Journal)
Introduction: Primary care physicians face the increasing burden of managing multimorbidities in an ageing population. Implementing an integrated care team (ICT) with defined roles and accountability to share consultation tasks is an emerging care model to address this issue. This study compared outcomes with ICT versus usual care for patients with multimorbidities in primary care. Methods: Data was retrospectively extracted from the electronic medical records (EMRs) of consecutive adult Asian patients empanelled to ICT and those in UC at a typical primary care clinic (polyclinic) in eastern Singapore in 2018. The study population had hypertension, and/or hyperlipidaemia and/or type 2 diabetes mellitus (T2DM). Clinical outcomes included the proportion of patients (ICT vs. UC) who attained their treatment goals after 12 months. Process outcomes included the proportion of patients who completed annual diabetic eye and foot screenings, where applicable. Results: Data from 3,302 EMRs (ICT = 1,723, UC = 1,579) from January 2016 to September 2017 was analysed. The ICT cohort was more likely to achieve treatment goals for systolic blood pressure (SBP) (adjusted odds ratio [AOR] = 1.52, 95% confidence interval [CI] = 1.38–1.68), low-density lipoprotein cholesterol (AOR = 1.72, 95% CI = 1.49–1.99), and glycated haemoglobin (AOR = 1.28, 95% CI = 1.09–1.51). The ICT group had higher uptake of diabetic retinal screening (89.1% vs. 83.0%, P < 0.001) and foot screening (85.2% vs. 77.9%, P < 0.001). Conclusion: The ICT model yielded better clinical and process outcomes than UC, with more patients attaining treatment goals.